Editorial - Clavijo, Amparo (Colombian Applied Linguistics Journal, 2010)
We are pleased to present our readers with volume 12, No. 2 of the Colombian Applied Linguistics Journal. This volume presents four research studies on Critical Literacy and a study on the interlanguage of Turkish EFL learners through the use of complaints. As teacher educators and researchers, one of the goals of our Language Teacher Education program in Applied Linguistics to TEFL is to help teachers reflect upon the need to promote critical pedagogies and literacies in schools. We believe that critical literacy “connects the political, and the personal, the public and the private, the global and the local, the economic and the pedagogical, for rethinking our lives and for promoting justice in place of inequity” Shor (1997, p. 2). Therefore, it is of paramount importance to make the results of critical pedagogy practices carried out by classroom teachers visible through our publication.